FRI0412 Urinalysis Findings and Renal Pathology in Japanese Patients with Lupus Nephritis. (10th June 2014) - Nakanishi, K.; McGill, R.L.; Kinjo, M.
Abstract : Background: Renal biopsy is crucial to establish the pathologic classification of lupus nephritis (LN), but urinalysis is usually evaluated first. Active urinary sediment (hematuria or cellular casts) is conventionally interpreted as evidence for proliferative LN (Class III or IV), whereas nephrotic range proteinuria (>3.5 g per day) suggests membranous LN (Class V). Objectives: The aim of this study was to correlate urinalysis findings with renal pathology in Japanese patients with LN. Methods: Medical records were reviewed at Okinawa Chubu Hospital to locate all patients with systemic lupus erythematosus who had a renal biopsy from 2001 to 2013. After exclusion of two patients with missing urinalyses, 83 biopsies performed on 66 patients were included. Data were collected on clinical features, medications and laboratory data. Results: Mean age was 32 ± 14 years; 57 of 66 (86%) were female. Active urinary sediment was reported in 53 of 83 (64%); nephrotic range proteinuria in 26 of 83 (31%) and sub-nephrotic range proteinuria (0.5 to 3.5 g per day) in 45 of 83 (54%). Discrepancies between urinalysis findings and renal pathology were common (Table). Active urinary sediment was absent in 13 of 52 (25%) of patients with Class IV or IV/V and 4 of 9 (44%) with Class III or III/V. Nephrotic range proteinuria was seen more often in Class IV (16 of 39, 41%) than Class V (4 of 12, 33%), although this difference was not statistically significant (P=0.63). Proteinuria was sub-nephrotic or absent in 21 of 29 (72%) with Class V, III/V or IV/V. Conclusions: Among patients with biopsy-proven LN, conventional interpretations of urinalysis findings were frequently discordant with renal pathology. Membranous LN was predominantly non-nephrotic and proliferative LN was non-nephritic in one-quarter of cases. These data suggest that a renal biopsy is necessary for accurate diagnosis of patients with suspected LN. References: Austin HA. Clinical evaluation and monitoring of lupus kidney disease. Lupus 1988; 7(9):618-621. Hahn BH, McMahon M, Wilkinson A, et al. American college of rheumatology guidelines for screening, treatment, and management of lupus nephritis. Arthritis Care Res (Hoboken). 2012; 64:797-808. Weening JJ, D'Agati VD, Schwartz MM, Seshan SV, Alpers CE, Appel GB, Balow JE, Bruijn JA, Cook T, Ferrario F, et al. The classification of glomerulonephritis in systemic lupus erythematosus revisited. J Am Soc Nephrol. 2004; 15(2):241–250. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2834